Fenomena Internalisasi Social Commerce: Studi Fenomenologi terhadap Pengalaman Hidup Mompreneur UMKM Subsektor Fashion di Kota Makassar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to reveal the essence of the life experiences of mompreneurs in the fashion sub-sector of Makassar City in terms of their sense of self and economic independence amid the intervention of digital technology in their domestic lives. The research method used is qualitative with a Heideggerian phenomenological approach to understand the subject as Dasein. Data were collected through semi-structured in-depth interviews, participatory observation, and documentation of 6 key informants selected using purposive sampling techniques with criteria as owners-managers of fashion MSMEs who have been actively using social commerce for at least five years. Data analysis was conducted interactively through the stages of condensation, data presentation, and conclusion drawing and verification using the Miles, Huberman, and Saldaña model. The results of the study show that the internalisation of social commerce has reached the stage of embodiment, where digital devices are no longer merely communication tools but existential extensions that are integrated with domestic activities. This phenomenon triggers extreme permeability between personal and professional spaces, but is successfully negotiated positively by informants as a means of self-actualisation and improved emotional well-being.